A Study of the Knowledge-Level of Farmers and Agricultural Extension Agents by Integrated Pest Management of Olive Orchard in Daraa and Homs Governorates (Damascus University Journal of agriculture sciences, 2022)
This research aimed at identifying some personal characteristics of farmers and agricultural extension agents working in extension units, and study the knowledge-level of farmers  and agricultural extension agents by Integrated Pest Management of olive orchard in Daraa and Homs Governorates, Data were collected from March to September in 2017. Randomly selected sample of 100 farmers and 49 agricultural extension agents from many villages in Homs ( Alrkama, Alzafrana, Tlkalah, Alnasera, Almoshrafeh) and 100 farmers and 43 agricultural extension agents from many villages in Daraa (Tesel, Daell, Mohjah, Alsheah saed, Ezraa,Nawa) were chosen and interviewed individually and subjected for questionnaires by using form prepared by the researchers. The results showed a low knowledge-level for farmers by IPM and medium knowledge-level for agricultural extension agents.   the result of this study recommended that agricultural extension must take extra role for educational and a wariness of olive farmers and transfer the agricultural technology to them through prepare scientific and practical plan helps to spread IPM.
Keywords: Integrated Pest Management; Knowledge